A new modeling approach of Myxococcus xanthus bacteria using polarity-based reversals* - Bloch Hélène; Calvez Vincent; Gaudeul Benoît; Gouarin Loïc; Lefebvre-Lepot Aline; Mignot Tâm; Romanos Michèle; Saulnier Jean-Baptiste (ESAIM: Proceedings and Surveys)
The aim of this paper is to model the collective behavior of Myxococcus xanthus bacteria to better understand the emerging patterns at the level of the colony. We use image analysis and data treatment on experimental data of Myxococcus xanthus bacteria. We develop two models whose main novelty is the polarity-based reversals. The first model is based on contact dynamics approach and the second one is inspired by a molecular dynamics approach. We compare the two models and we show numerical simulations in 2D. The mathematical and biological aspects of each model are discussed.